2013
DOI: 10.1007/s00421-013-2645-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of training on markers of platelet activation in response to a bout of heavy resistance exercise

Abstract: Recent connections between platelet activity and cardiovascular disease have raised questions of whether platelet function varies in exercising individuals. Resistance training has been linked to a possible reduction in hyper-aggregability of platelets, especially following acute strenuous exercise. The present investigation was designed to explore the effects of an acute resistance exercise test on the primary hemostatic system in both resistance-trained (RT) and untrained (UT) individuals. Ten RT (five men a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 41 publications
1
14
2
Order By: Relevance
“…This was comparable with a previous study which showed a significant increase in VWF:Ag levels post exercise and 15 minutes after exercise [35]. We found a higher increase in VWF:Ag response upon exercise in males compared with females.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This was comparable with a previous study which showed a significant increase in VWF:Ag levels post exercise and 15 minutes after exercise [35]. We found a higher increase in VWF:Ag response upon exercise in males compared with females.…”
Section: Discussionsupporting
confidence: 92%
“…The highest VWF:Ag response in individuals with the lowest physical fitness underlines the hypothesis that frequent physical exercise has a positive effect on cardiovascular risk. This is in contrast with a previous study which showed no difference in VWF:Ag increase upon exercise between resistance trained and untrained individuals [35]. However, in this study only a small number of individuals were included (N = 20).…”
Section: Discussioncontrasting
confidence: 63%
“…Our study showed a significant decrease in the values of vWF both in the males (p < 0.005) and females (p < 0.001) with diabetes mellitus type 2 after EWET and these results correlated with recent researches. Creighton et al 21 explored the effects of an acute resistance exercise test on the primary hemostatic system both in resistance-trained and untrained individuals and concluded that reduced vWF in both groups may be attributed to the training status. Androulakis et al 22 examined whether a high volume of training could lead to the endothelial activation and/or dysfunction in professional soccer players due to exercise-induced oxidative stress and vWF antigen plasma levels were measured 1 day before and after 7 weeks of strenuous exercise.…”
Section: Discussionmentioning
confidence: 99%
“…In the first hour postexercise, resistance-trained individuals displayed significantly reduced platelet activation, in terms of lower βTG levels, compared with untrained individuals. 47 Of note, PF4 and βTG radioimmunoassays and ELISAs are associated with some methodological difficulties. 43,48 An alternative analysis method for platelet activation is whole blood flow cytometry using antibodies against platelet activation markers, for example, glycoprotein (GP) Ib and GPIV.…”
Section: Platelet Activitymentioning
confidence: 99%